Peningkatan Hasil Belajar Pendidikan Agama Islam Dengan Menerapkan Model Pembelajaran Kolaborasi Pada Siswa Kelas III SDN 21 Pilubang - Ali Imran; Putri Ayu; Zomiliarif; Dewi Kurnia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to determine the steps for implementing a collaborative learning model in Islamic Education (PAI) lessons in grade III at SDN 21 Pilubang and to identify the improvement in learning outcomes achieved. This study uses the Classroom Action Research (CAR) method with grade III students as subjects on the material “Understanding Sentences in the Qur'an.” The results showed that the application of the collaborative learning model could significantly improve student learning outcomes. At the beginning (pre-test), 15 students scored below 65 and only 9 students scored above 65. After the intervention in cycle I, learning outcomes improved, with 10 students scoring above 65, 6 students scoring 65, and 8 students still scoring below 65. Improvements in cycle II showed even better results, with 20 students scoring above 65, while only 4 students still scored below 65. The percentage of learning completeness also increased from 38% in the pre-cycle, 67% in cycle I, and 83% in cycle II. Thus, the application of the collaborative learning model proved to be effective in improving the PAI learning outcomes of third-grade students at SDN 21 Pilubang in accordance with the expected objectives.